Modern methods of diagnostics and control of treatment efficacy new-onset with fibro-cavernous pulmonary tuberculosis, induced with Mycobacterium multidrug-resistant - M. M. Nikitin; A. S. Puz’ko; P. V. Senchikhin; A. A. Glotov (Вестник рентгенологии и радиологии)
A clinical case of successful treatment of newly diagnosed fibro-cavernous pulmonary tuberculosis, caused by Mycobacterium tuberculosis with multidrug resistance, is presented. Monitoring of effectiveness of treatment with modern high-tech radiation methods is submitted. The necessity of an individual approach to the treatment of tuberculosis in these patients is shown.